Suxamethonium-Induced Hyperkalemia: A Short Review of Causes and Recommendations for Clinical Applications - Henrik Lynge Hovgaard; Peter Juhl-Olsen (Critical Care Research and Practice)
After the introduction of suxamethonium in 1953, cases of cardiac arrest during induction of anesthesia were recorded. In the following years, hyperkalemia was identified as the cause, and the connection to acetylcholine receptor modulation as the underlying molecular mechanism was made. Activation of the acetylcholine receptor with suxamethonium, acetylcholine, or choline causes an efflux of potassium to the extracellular space. However, certain pathological conditions cause acetylcholine receptor proliferation and the emergence of immature receptors capable of a larger potassium efflux to the bloodstream. These pathologic conditions include upper and lower neuron injuries, major burns, trauma, immobility, muscle tumors, muscular dystrophy, and prolonged critical illness. The latter is more important and relevant than ever due to the increasing number of COVID-19 patients requiring prolonged respiratory support and consequent immobilization. Suxamethonium can be used safely in the vast majority of patients. Still, reports of lethal hyperkalemic responses to suxamethonium continue to emerge. This review serves as a reminder of the pathophysiology behind extensive potassium release. Proficiency in the use of suxamethonium includes identification of patients at risk, and selection of an alternative neuromuscular blocking agent is imperative.